2021
DOI: 10.3897/phytokeys.185.72259
|View full text |Cite
|
Sign up to set email alerts
|

Leaf epidermal micromorphology in Aspidistra (Asparagaceae): diversity and taxonomic significance

Abstract: Micromorphological characters of leaf epidermis were investigated in 69 species of Aspidistra using scanning electron microscopy. Sculpture of epidermis varies from smooth to verrucose and rugose in the genus. The abaxial epidermis of some species bears papillae, whereas the adaxial surface uniformly lacks the papillae. Sculpture type of epidermis and density of papillae are generally found to be stable characters at a species level. The infraspecific variation of epidermis sculpture, where present, ranges fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The results of this study showed that the number and structure of leaf epidermal appendages showed rich diversity, such as epidermal wall pattern, epidermal cell density, stomatal density and stomatal index, etc. There were some significant differences among the ten wild peonies in the epidermal morphology, which could be used to identify the wild tree peonies even if they have no flowers or fruits [46,51,52]. Besides, the morphological characteristics of the epidermis, especially the epidermal hairs and stomata, had a certain taxonomic value for the classification of wild tree peonies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the number and structure of leaf epidermal appendages showed rich diversity, such as epidermal wall pattern, epidermal cell density, stomatal density and stomatal index, etc. There were some significant differences among the ten wild peonies in the epidermal morphology, which could be used to identify the wild tree peonies even if they have no flowers or fruits [46,51,52]. Besides, the morphological characteristics of the epidermis, especially the epidermal hairs and stomata, had a certain taxonomic value for the classification of wild tree peonies.…”
Section: Discussionmentioning
confidence: 99%
“…As a new attempt to bring light into the mystery of intrageneric relationships, Vislobokov et al (2021) investigated the micromorphology of the leaf epidermis in 73 species using scanning electron microscopy. Here, again, micromorphological traits show a certain degree of diversity, but are not in general congruence to floral characters or geographic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Aspidistra (Asparagaceae) is one of the represented plant groups of evergreen perennials in limestone karsts, with a center of diversity in southwest China and northern Vietnam [7]. Over the last forty years, the number of recognized Aspidistra species has experienced a remarkable increase [8], rapidly rising from 11 (until the year 1978) [9] to more than 200 [10][11][12][13]. However, the diversity of Aspidistra is still far from being revealed, with more new species being discovered during field investigations every year [8,11,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Chun & F.C. How) [10,19]. In most cases, accurate identification of Aspidistra is almost impossible in non-flowering conditions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation